Co-pyrolysis characteristics and kinetic analysis of organic food waste and plastic. (February 2018) - Tang, Yijing; Huang, Qunxing; Sun, Kai; Chi, Yong; Yan, Jianhua
Highlights: The co-pyrolysis of nitrogen enriched food waste and PVC will reduce the content of nitrogen-containing components in tar. Both TGA and fixed-bed experiments were carried out to estimate the co-pyrolysis behavior. The interaction could accelerate reaction rate and decrease the activation energy compared with calculated results. The interaction promoted the formation of heavier tar components. Results indicate a troublesome effect during co-pyrolysis. Sorting and dechlorination should be adopted before pyrolysis. Abstract: In this work, typical organic food waste (soybean protein (SP)) and typical chlorine enriched plastic waste (polyvinyl chloride (PVC)) were chosen as principal MSW components and their interaction during co-pyrolysis was investigated. Results indicate that the interaction accelerated the reaction during co-pyrolysis. The activation energies needed were 2–13% lower for the decomposition of mixture compared with linear calculation while the maximum reaction rates were 12–16% higher than calculation. In the fixed-bed experiments, interaction was observed to reduce the yield of tar by 2–69% and promote the yield of char by 13–39% compared with linear calculation. In addition, 2–6 times more heavy components and 61–93% less nitrogen-containing components were formed for tar derived from mixtures.